Optimalisasi Program Remaja Islam Masjid dalam Meningkatkan Kualitas Remaja di Kecamatan Malangbong Garut - Nursolih, Muhsin; Saepuloh, Uwoh; Rahman, Arif (Tadbir: Jurnal Manajemen Dakwah, 2023)
Remaja Islam Masjid Al-Ilyas is youth organization under auspices of the DKM Al-Ilyas Mosque Malangbong. Programs and activities have a positive impact on youth. The purpose study to find out (1) the steps of program planning (2) setting goals, and (3) the efforts improving the quality of youth. The research based on S Rao's theory that optimization is a plan, goal, and effort obtain maximum results. Research method used descriptive method. The results study are (1) program planning steps, taking elements of 5W + 1H planning (2) setting goals for forming young Muslim cadres, role of da'wah younger generation, and applying good values (3) Then, the efforts in improving quality of youth, including carrying out training-based, social and religious-based activities.